Investigation of Electrochemical Discharge Machining for Tungsten Carbide: Effects of Electrolyte Composition on Material Removal Rate and Surface Quality - Najm Vian N.; Abbas Tahseen F.; Aghdeab Shukry H. (Management Systems in Production Engineering)
Tungsten carbide (WC-Co) with a cobalt binder has been widely used in industrial application. Through their high wear resistance and hardness, which make it a challenge to machine. Electrochemical discharge machining (ECDM) is a newly developed hybrid technique used to machine conductive and nonconductive materials. Tungsten carbide machining is an area that needs more investigation. In this study, different types of electrolytes have been tested in the electrochemical machining of tungsten carbide. It has been concluded that tungsten carbide was successfully machined with electrolytes that were either neutral salts or a combination of neutral salts and hydroxides, the highest material removal rate achieved was (0.09250 g/min), and the average surface roughness achieved in this work was measured at (Ra 0.9275 µm). However, deposition took place on the surface of machined tungsten carbide when the samples were treated with sodium hydroxide and potassium hydroxide. EDX analysis of successfully machined tungsten carbide samples reveal the presence of carbon (C) due to diffusion from the base material and oxygen (O), most likely due to oxidation brought on by the high temperatures utilized. Scanning electron microscopy confirmed that the machined surfaces had craters, pores, restricted microcracks, and re-deposited melt particles, among other things.